Educational Self-Esteem Research Over the Last 50 Years: A Bibliometric Analysis of the Scopus Database - Hanif Alyaa Nabilla; Djamilah Bondan Widjajanti; Raden Rosnawati (MASI Mandiri Edukasi, 2025)
This study aims to analyse research trends on children's self-esteem education. This study uses the keywords